KOMPETENSI PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM DALAM PENINGKATAN KUALITAS PELAKSANAAN EVALUASI PEMBELAJARAN - Ibrohim (UNISAN JURNAL, 2024)
This exploration intends to figure out how the board creates impressive skill and increments acquiring adequacy. This exploration utilizes a subjective plan. Information assortment procedures use meetings, perception and documentation. From the show and information investigation it very well may be closed as follows: 1) The execution of instructor proficient advancement the executives at SMAIT TQ Ihya Assunnah to increment learning adequacy has been completed by the means. The arranging stage for instructor proficient improvement starts with gathering information through perception and checking on educator records, as well as arranging an instructor proficient improvement program that is custom fitted to the issues instructors face. The preparation and advancement stage incorporates a few exercises, specifically: 1) sorting out the MGMP strengthening program (Subject Educator Consultation), 2) carrying out preparing and courses in the In help preparing program, 3) standard conversations between subject instructors like clockwork at On preparing administration program, 4) giving support to educators to work on their schooling, 5) giving honors to instructors who accomplish accomplishments and approvals for the people who need discipline or low execution, 6) including instructors in each madrasa improvement, and 7) tolerating and creating thoughts and potential that the educator has.